Piracy on the High Seas - Sugiharto, Rudy; Victoria, Ong Argo (IWTJ : International Water Transport Journal, 2020)
Piracy on the high seas, both by foreign ships and by domestic vessels in international waters, has recently caused unrest for international shipping. The prosecution of the high sea piracy crime is based on the enactment of international law relating to piracy in the high seas. The problems raised in this research are how to regulate piracy on the high seas based on international law, how is the MV Jahan Moni piracy and how are the efforts to deal with piracy problems on the high seas in the case of the MV Jahan Moni ship? The research method is carried out by normative legal research or literature law research conducted by examining library materials and empirical legal research. The legal research used is normative legal research or also known as library research with secondary data collection from magazines, books, journals, newspapers, online websites, and other library documents. Based on the explanation that has been described in previous chapters, it can be concluded that the following actions are piracy in the high seas initially and generally are motivated by economic factors. However, in its development and in today's situation, the phenomenon of piracy is in the context of acts of violence in the wider high seas. This is due to the increasing possibility of the threat of acts of terrorism in the two Strait with the background of non-economic problems, where it is very possible that these actions were also carried out on the high seas, as well as ships at sea. Piracy arrangements on the high seas are based on international law, namely based on the 1982 UN Convention on the Law of the Sea.